Розвиток ринкових відносин на основі квазіінтеграції - Солнцев, С. О.; Жигалкевич, Ж. М. (Видавництво Львівської політехніки, 2016)
Розкрито сутність квазіінтеграції. Проаналізовано різні підходи до причин об'єднання установ в інтегровані структури. Виявлено фактори формування квазіінтеграційних структур, а саме: ринкові фактори, мінливість зовнішнього середовища, контекстні фактори економіки, спрямованість на економіку знань, орієнтація на інформаційний простір, реалізація технологічних укладів, впровадження підривних технологій, актуалізація міжфірмових партнерських взаємин, використання методології передбачення, отримання синергетичних ефектів. Подано перелік характерних ознак та форм квазіінтеграції. Встановлено перспективність квазіінтеграції взаємодіючих підприємств як основи розвитку ринкових відносин. The essence of kvaziintegration is expanded in the article. Kvaziintegration refers to the universal (hybrid) process of corporate formation, which combines features of both integration and disintegration. This is a formal (imaginary) integration on a conventional basis, which leaves the autonomy to parts that belong to it. The advantage of this harmonious formation is a partnership and absolute competition. The phenomenon of kvaziintegration’s structure is laying in its special features – it’s adaptive, flexible, dynamic formation and focuses on tactical targets. Kvaziintegrational structures – are voluntary partner unions of cooperating manufactures and scientific (research-scientific, technological-scientific, technical-scientific) institutions on the basis of comprehensive utilization of available resources that are targeted to achieve the greatest economic efficiency and strengthen market positions which peculiarity is no control over the property assets. Different ircumstances of why institutions are integrating into structures are analyzed: targeted similarities of real operating business entities (e.g. providing competitive advantages, optimal use of resources, strengthening market position, etc.); the need of governmental support; the need to attract investments for developing markets (which include, for instance, capital construction area); the need to enhance opportunities for business innovation; development of informational and communicational technologies; aim to obtain a synergistic effect; development of benchmarking concept that focuses on studying business structures and constructive accumulated experience use of leading business areas; development of partnership ideology. Factors of Kvaziintegrational structures formation are revealed, for instance: market factors, the variability of the environment, economics contextual factors, focus on the knowledge economics, focus on the information space, implementation of technological stages and disruptive innovations, constant update on intercompany’s partnerships, use of the foresight methodology, synergy effect gaining. List of Kvaziintegration’s characteristics and forms is provided: multiplicity of economic agents; control on behavior of formally independent enterprises with no control over its property; enterprise’s specialization of Kvaziintegrational structures; functional correlation and interaction of participants; innovative orientation; possibility of informational / transactional costs reduction; increased market opportunities; presence of competition within kvaziintegrational structure; infrastructure provision; accelerated information circulation; increased competi tiveness on domestic and foreign markets; reduced risks; highly qualified staff. Defined that kvaziintegrational structures – are a network formations that are being manifested in various forms: strategic alliances, Network associations, clusters, virtual enterprises, creating value networks, etc., which are based on stable partnership relations. Partnership relations – are contractual relations that are established between entrepreneurs and are giving opportunity to each of them to get the desired level of profit by sharing the results of operational activity (purchase, delivery of products) which appears in goods or money equivalent. Based on the analysis perspective opportunities of cooperating companies’ kvaziintegration as the basis of market relations are proved.
Market relations development on a quasi-іntegration basis
Keywords: інтеграція; квазіінтеграція; квазіінтеграційна структура; фактор; партнерство; ринкові відносини; integration; quasi-іntegration; quasi-integration structure; factor; partnership; market relations